EVALUATION OF TRANSFORMATIVE SKILLS IN PATIENTS WITH GONARTHROSIS IN PHYSIOTHERAPY PROGRAMS - Rusnac Felicia (Sport şi Societate)
This study explores an innovative dimension in the rehabilitation of patients with gonarthrosis by assessing transformative skillswithin physiotherapy programs. Gonarthrosis, characterized bythe progressive degeneration of the knee joint, results in significant dysfunction, adversely affecting patients' quality of life. Physiotherapy is recognized for its ability to alleviate symptoms and enhance functionality; however, long-term outcomes canvary considerably based on the active involvement of the patient and the development of essential skills known as transformative skills. These skillsinclude self-motivation, resilience, self-awareness, and the ability to adapt to changes brought about bythe illness, which are crucial determinants of successful, effective, and lasting rehabilitation.Through a specific assessment system, this study analyzes the role of transformative skillsin physiotherapy programs designed for patients with gonarthrosis, investigating how these skillsinfluence both patient engagement and physical recovery outcomes. The integrated approach to psychological and motivational dimensions provides a new perspective on optimizing therapeutic interventions, targeting not only functional recovery but also enhancing patients' capacity to maintain therapeutic progress in the long term.The study highlights the potential of incorporating transformative skillsinto physiotherapy programs, contributing to the development of more effective and personalized strategies for treating gonarthrosis, positively impacting patients' quality of life and the overall efficiency of the recovery process.